FarMoRe – A tool for monitoring and reporting GHG mitigation results in rice production - Trang, Vu Hong; Nelson, Katherine; Yen, Bui Tan; Cuong, Ong Quoc; Tran, Nguyen Bao; Quyet, Vu Manh (International Rice Research Institute, 2024)
Vietnam has made strong commitments to reduce Greenhouse gas (GHG) emissions. In its Nationally Determined Contributions, Vietnam has set ambitious targets of reducing 12.4 MtCO2e from agriculture with domestic resources and additional 50.9 MtCO2e with international support. Additionally, Vietnam has joined the Global Methane Pledge and committed to take actions to reduce methane emissions by 30% by 2030 compared to the 2020 levels. According to Vietnam’s Third Biennial Updated Report, the Agriculture, Forestry and Other Land Use (AFOLU) sector contributed to 62% of the country’s methane emissions in 2016. Rice cultivation was the largest methane source, responsible for 75% of CH4 emissions from the AFOLU sector. Therefore, the rice sector is a priority to achieve the nation’s mitigation targets. To achieve verifiable mitigation results in the rice sector, effective tools to track and validate GHG mitigation progress and outcomes are crucial. This requires monitoring rice farming activities at field levels to (1) estimate GHG emissions season to season, and (2) introduce interventions or improved low-emission practices properly. Farm household surveys are generally cost and labour intensive and thus not sustainable in the long run. The Farm Activity Morning and Reporting (FarMoRe) tool, developed by the International Rice Research Institute with support of IFAD-EU, offers a cost-effective solution. FarMoRe provides a standardized set of questions aligned with IPCC protocols for collecting data required for GHG calculations. The tool automates these calculations, presenting GHG emissions (kg CO2e/ha/season) immediately after data submission. Beyond emissions data, FarMoRe offers valuable insights into field management practices like seed rate, fertilizer use, and aeration periods – all factors influencing GHG emissions. The tool visualizes this data alongside scientific thresholds that could suggest potential for improvement. FarMoRe also stores farmers' seasonal GHG emissions data, enabling them to track progress and compare their performance with area averages. Recognizing the context-specific nature of farming, the tool allows users to set their own benchmarks for a more tailored approach. FarMoRe offers several benefits. It reduces the workload for data collection, calculation, and storage, saving time and resources for both farmers and researchers. The tool ensures reliable data for monitoring mitigation progress and outcomes. Additionally, FarMoRe data can be used to validate aggregated data collected from other sources and remote sensing technologies. The tool's scalability allows application across various farm sizes, from individual households to cooperatives and production units. FarMoRe has been tested in Can Tho city of Vietnam and received positive feedback on its usability. By streamlining data collection, analysis, and visualization, FarMoRe presents a valuable tool for large-scale rice GHG mitigation programs, such as the recently approved project of Developing 1 million hectares of high quality and low-emission rice associated with green growth in the Mekong Delta of Vietnam. This technology supports sustainable rice production practices and has the potential to contribute significantly to achieving Vietnam's environmental goals.